Comparison of the finger-feeding versus cup feeding methods in the transition from gastric to oral feeding in preterm infants - Cláudia M.D. Moreira; Regina P.G.V. Cavalcante-Silva; Cristina I. Fujinaga; Francine Marson (Elsevier, 2017)
Objectives: To assess the finger-feeding technique when compared with the cup feeding method during the early stage of preterm infant feeding transition regarding milk loss, milk ingestion period, and complications. Methods: Experimental, randomized, prospective study including 53 preterm infants with gestation age < 37 weeks, clinically stable, and with a score of >28 points in the Oral Feeding Readiness Assessment Scale. The preterm babies were randomized to be included in the control group, which underwent the feeding transition using a cup or in the experimental group, which used the finger-feeding technique. The analysis of data was performed using Student's t-test to evaluate differences between mean values of the appointed variables, and Fischer's test for categorical variables; the asymmetric variables were assessed by the Kruskal-Wallis ANOVA test. Results: When compared with the control group, the experimental group showed lower milk loss, longer milk ingestion time, and a lower frequency of complications during feeding. The significance level was set at 5%, with a confidence interval of 90%. Conclusion: The finger-feeding technique was shown to be a better feeding transition method regarding efficacy when compared with cup feeding method, due to lower milk loss and fewer complication episodes. Resumo: Objetivo: Avaliar a técnica sonda-dedo em comparação ao copo no início da transição alimentar do prematuro quanto à perda de leite ofertado, tempo de ingestão e complicações. Métodos: Estudo experimental, randomizado, não cego, prospectivo com 53 prematuros de idade gestacional <37 semanas, clinicamente estáveis e com escore >28 pontos na Avaliação da Prontidão para início da alimentação por via oral. Os prematuros foram randomizados para o Grupo Controle que realizou a transição alimentar com o copo e para o Grupo Experimental que utilizou a técnica sonda-dedo. Na análise dos dados, foram aplicados o teste t de Student para avaliar a diferença de médias e o teste exato de Fisher para as variáveis categóricas, enquanto para as variáveis assimétricas foi aplicado a Anova de Kruskal-Wallis. Resultados: O grupo experimental apresentou em relação ao grupo controle, diferença significativa quanto a menor perda de leite, maior tempo de dieta e menor frequência de complicações. O nível de significância foi de 5% e poder de teste mínimo de 90%. Conclusão: A técnica sonda-dedo mostrou-se um método alternativo de transição alimentar superior em sua eficiência quanto a menor perda de leite e menor incidência de complicações. Keywords: Preterm, Sucking behavior, Feeding methods, Palavras-chave: Prematuro, Aleitamento materno, Métodos de alimentação